1993
DOI: 10.1093/hmg/2.2.165
|View full text |Cite
|
Sign up to set email alerts
|

High rate of multilocus deletion in a human tumor cell line

Abstract: The nature of recessive mutations at the autosomal locus encoding the purine salvage enzyme adenine phosphoribosyl transferase (APRT) was analyzed in a highly malignant human tumor cell line (the colorectal carcinoma line SW620). Mutant strains resistant to the purine analog 8-azaadenine were obtained in two steps. The first step selection for partial drug resistance produced strains hemizygous for APRT as a result of high frequency loss of one allele. In the second step selection, low frequency base substitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…There seems little doubt that some sporadic cancers do have raised intrinsic mutation rates (18)(19)(20). Our models suggest four main ways in which this can occur.…”
Section: Methods and Resultsmentioning
confidence: 83%
“…There seems little doubt that some sporadic cancers do have raised intrinsic mutation rates (18)(19)(20). Our models suggest four main ways in which this can occur.…”
Section: Methods and Resultsmentioning
confidence: 83%
“…This colorectal carcinoma cell line has no detectable microsatellite instability and low rates of point mutation at selectable loci (Table 1) (4,17). On the other hand, SW620 has a high rate of multilocus deletions that result in loss of one copy of the APRT gene (16,17). Base substitutions at APRT in DLD-1 were compared with those occurring in HUS12, a derivative of SW620 having a single copy of the APRT gene.…”
Section: Resultsmentioning
confidence: 99%
“…Extent of the LOH events. In the mismatch-repair-proficient line SW620 the loss of one APRT allele occurred at a high rate (6 ϫ 10 Ϫ6 [16]). Using a TaqI polymorphism present in intron 2 of the APRT gene, we demonstrated that there was no difference in the rate of loss of either of the two APRT alleles even though one of the APRT genes was present on a rearranged chromosome.…”
Section: Resultsmentioning
confidence: 99%
“…For example, SW620 cell line shows very low rates of base substitution but exhibits a substantially altered karyotype and high rates of multilocus deletion (25,37). This cell line also displays an unusual mechanism of mutation in the form of multiple base substitutions or fiame-shifts that apparently occur as a result of a single initiating event (25).…”
Section: Microsateflite Instability In Colorectal Carcinoma Ceilmentioning
confidence: 99%